The climate of rebellion in the early modern Ottoman Empire - White, Sam, 1980-; Cambridge University Press (New York : Cambridge University Press, 2011)
"This book explores the serious and far-reaching impacts of Little Ice Age climate fluctuations in Ottoman lands"--
"This book tells how extreme cold and drought during the Little Ice Age along with rising population pressure and resource shortages created a serious rebellion in the Ottoman Empire in the 1590s. It argues that the rebellion was a major turning point for the Ottomans, reversing more than a century of imperial growth and expansion, and leading to millions of deaths. Over the 1600s, recurring climate fluctuations, nomad invasions, rural flight to cities, and outbreaks of disease kept the empire from recovering. This book is the first to look at the impact of climate on Middle East history and one of the first to look at the environmental evidence and interdisciplinary perspectives and offers a major reinterpretation of a central period in Ottoman history"--
-- Pt. 1. An imperial ecology -- Regions, resources, and settlement -- Growth and its limits -- Disasters of the later sixteenth century -- Land at the margins : Karaman and Larende -- part 2. The Little Ice Age crisis -- The Little Ice Age in the Near East -- The great drought -- The Celali Rebellion -- In the wake of the Celalis : climate and crisis in the seventeenth century -- part 3. Ecological transformation -- Desert and snow -- City and country -- Provisioning and commerce -- Conclusion
Includes bibliographical references and index
Keywords: Climatic changes -- Social aspects -- Turkey -- History; Social change -- Turkey -- History; Social conflict -- Turkey -- History; Turkey -- History -- Ottoman Empire, 1288-1918; Turkey -- Environmental conditions; Turkey -- Climate -- History; Turkey -- Population -- History; Natural resources -- Turkey -- History; Natural resources -- Turkey -- Management -- History